A framework for variable amplitude corrosion fatigue materials tests for offshore wind steel support structures. (24th March 2014) - Brennan, F. P.; Pantelakis, Spiros; Berto, Filippo; Lazzarin, Paolo
ABSTRACT Climate change and sustainability have driven enormous development programmes for offshore wind. These large structures are mainly fabricated of welded steel tubular and plate sections not dissimilar to structural details commonly encountered in the ship, and offshore oil and gas sectors, but design requirements differ significantly due to environmental aspects, loading regime and low capital expenditure and operational expenditure requirements. There is therefore a requirement to quickly update corrosion fatigue knowledge and data bases in order to assist operations and designers to optimise structures with respect to fatigue strength and cost. This paper reviews seawater corrosion fatigue and potential approaches to developing appropriate test procedures and analysis methods to produce reliable and meaningful corrosion‐fatigue behaviour under stochastic loading conditions and sets out some fundamental principles for any such testing programme.